1996
DOI: 10.1099/13500872-142-3-469
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in Membrane Fluidity and Lipid Composition, and Modulation of H+-ATPase Activity in Saccharomyces Cerevisiae caused by Decanoic Acid

Abstract: Decanoic acid, a lipophilic agent, inhibited in w i b o the plasma membrane H+-ATPase of Sacchammyces cemwisiae grown in YPD medium. Conversely, when decanoic acid (35 pM) was present in the growth medium, the measured H+-ATPase activity was four times higher than that of control cells. Kw and pH and orthovanadate sensitivity were the same for the two growth conditions, which indicated that H+-ATPase activation was not due to conformational changes in the enzyme. The activation process was not entirely reversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 32 publications
(46 reference statements)
2
69
1
Order By: Relevance
“…However, no clear ortholog of PDR12 exists in the C. albicans genome. Other possible resistance mechanisms include alteration of the plasma membrane lipid composition (47) or other as-yet-undocumented mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, no clear ortholog of PDR12 exists in the C. albicans genome. Other possible resistance mechanisms include alteration of the plasma membrane lipid composition (47) or other as-yet-undocumented mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Similar changes in the abundance ratio of unsaturated fatty acids have been found as part of the adaptation processes of yeasts to stress conditions. For example, S. cereuisiae increases the amount of oleic acid at the expense of palmitoleic acid as a response to the presence of decanoic acid (a toxin produced during fermentation) in the growth medium (Alexandre et al, 1996) and a similar response is observed in the presence of ethanol (Sajbidor & Grego, 1992). Also, work on 7'.…”
Section: Fatty Acidsmentioning
confidence: 99%
“…Several factors can lead to stuck fermentation, such as insufficient nitrogen, the low lipidic content of the grape must, and high concentrations of mediumchain fatty acids (MCFA) in the fermenting must (3). The main MCFA, octanoic and decanoic acids, are produced by yeasts during alcoholic fermentation as by-products of lipid synthesis (40).…”
mentioning
confidence: 99%
“…The toxicity of short-to mediumchain fatty acids also is correlated with their lipophilic properties, indicating a probable effect on the cell membrane (45). Indeed, decanoic acid, the more toxic of the two compounds (49), has been shown to increase membrane permeability (3). However, the rapid exposure of yeast cells to sublethal concentrations of octanoic acid provokes an adaptive response, allowing the cells to resist larger amounts of inhibitor (7).…”
mentioning
confidence: 99%